The effect of MIND diet on sleep status, mental health, and serum level of BDNF in overweight/obese diabetic women with insomnia: a randomized controlled trial - Mona Golmohammadi; Vahideh Ebrahimzadeh Attari; Yahya Salimi; Lotfollah Saed; Seyed Mostafa Nachvak; Mehnoosh Samadi (Scientific Reports)
Abstract Insomnia is common in type 2 diabetes mellitus (T2DM) and affects mental health and quality of life. The present study aimed to examine the efficacy of MIND (Mediterranean-DASH Intervention for Neurodegenerative Delay) diet on the anthropometric measurements, sleep quality, depression, anxiety, and serum levels of cortisol and brain derived neurotrophic factor (BDNF) in type 2 diabetic women with insomnia. This randomized controlled trial (RCT) involved 44 type 2 diabetic women with insomnia, aged 30 to 65 years, who were randomly assigned to be under the MIND low-calorie diet (n = 22) or a low-calorie diet (LCD) as the control group (n = 22) for 12 weeks. The above-mentioned variables were assessed at the beginning and the end of intervention. Following the MIND diet for 12 weeks accompanied by the significant decrease of waist circumference and significant improvement of sleep quality, depression, and anxiety compared to the control group. In addition, the MIND diet vs. LCD group exhibited a significant reduction in the cortisol levels and a significant increase in BDNF. This study provides promising evidence of the effectiveness of the MIND diet in improving the sleep quality, mental health, and some related biochemical parameters in diabetic women with insomnia. Trial registration: IRCT20181111041611N8.